PENGARUH PEMANTAUAN DIRI TERHADAP ALIENASI DIRI - Paramita, Metta; Ghofur, Gun Gun Abdul; Nurwanto, Haryadi (TALENTA, 2012)
The composing of the research is based on the developing culture in society. It results in various changes of behavior, life style, mobility, and values, which give numerous additions to the complexity of society. The arised psychological implication is the broad social-psychological insecurity, which causes an individu to experience a conflict and inability to adapt. This may result in self-alienation. To prevent this phenomenon, the individu needs toÂ  have an adequate ability of self-controlling in his every act. It is expected then, with the proper behavioral tendencies, the individu will be self-adapting which will result in society acceptance of the individu well-being. The acceptance will help in creating positive self-concept, and finally will help an individu to feel secure, both physically and mentally.